Speciation of selenium dietary supplements; formation of S-(methylseleno)cysteine and other selenium compounds - Amoako, Prince O.; Uden, Peter C.; Tyson, Julian F. (Analytica chimica acta, 2009)
Speciation of selenium is of interest because it is both essential and toxic to humans, depending on the species and the amount ingested. Following indications that selenium supplementation could reduce the incidence of some cancers, selenium-enriched yeast and other materials have been commercialized as supplements. Most dramatically however, the SELECT trial that utilized l-selenomethionine as the active supplement was terminated in 2008 and there is much debate regarding both the planning and the results of efficacy studies. Further, since dietary supplements are not regulated as pharmaceuticals, there are concerns about the quality, storage conditions, stability and selenium content in selenium supplements. Enzymatic hydrolysis enabled selenium speciation profiles to be obtained by high performance liquid chromatography with inductively coupled plasma mass spectrometry (HPLC–ICP-MS) and following derivatization gas chromatography with atomic emission detection (GC–AED). Coated fiber solid phase microextraction (SPME) was used to extract volatile selenium species for determination by GC–AED and GC–MS. Similar speciation patterns were observed between yeast-based supplements subject to extended storage and those heated briefly at elevated temperatures. All the yeast-based supplements and one yeast-free supplement formed S-(methylseleno)cysteine on heating. Evidence was obtained in support of the hypotheses that S-(methylseleno)cysteine is formed from a reaction between dimethyldiselenide and cysteine or cystine.